Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial El Limo, Cantón Puyango, Periodo 2022. - Rodríguez Gómez, Rocío Marifé (2024)
The present Work of Curricular Integration called Financial Audit to the Decentralized Parish Autonomous Government El Limo, Puyango Canton, Period 2022, was developed in order to evaluate the internal control system implemented by the entity, determine the reasonableness of the balances reflected in the financial statements and submit the audit report that will serve for the appropriate decision-making in the Institution. In order to meet the objectives, the process of the financial audit that began with the preliminary visit to obtain information and thus carry out the evaluation of the internal control system to the components Current assets was considered, non-current assets, liabilities, assets, income and expenses, programs and questionnaires were applied to verify that the activities were carried out in accordance with the laws and regulations in force, thereby establishing a high level of confidence, Moreover finalized the evaluation has been evidenced some weaknesses described in narrative documents. Analytical and summary sheets of the above- mentioned components were subsequently developed as part of the audit procedures, which made it possible to determine the reasonableness of the balances presented in the financial statements. Finally, the audit report containing the opinion, conclusions and recommendations was made, which will serve as a guide for the officials of the Parish GAD to take appropriate corrective measures. Among the most important findings found, it is evident that there is no segregation of incompatible functions; lack of codification of property owned by the Parish GAD; There are no policies and procedures for retaining supporting documents for accounts payable and expenses. It is suggested to develop procedures to verify and analyze all the activities and operations carried out by the institution, to identify possible deficiencies or inconsistencies in management and take corrective measures in accordance with current legal regulations.